2017
DOI: 10.3168/jds.2016-12243
|View full text |Cite
|
Sign up to set email alerts
|

Heritabilities of measured and mid-infrared predicted milk fat globule size, milk fat and protein percentages, and their genetic correlations

Abstract: The objective of this study was to estimate the heritability of milk fat globule (MFG) size and mid-infrared (MIR) predicted MFG size in Holstein cattle. The genetic correlations between measured and predicted MFG size with milk fat and protein percentage were also investigated. Average MFG size was measured in 1,583 milk samples taken from 254 Holstein cows from 29 herds across Canada. Size was expressed as volume moment mean (D[4,3]) and surface moment mean (D[3,2]). Analyzed milk samples also had average MF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
2
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 24 publications
(26 reference statements)
3
2
4
Order By: Relevance
“…The average genetic correlation between MFGS MIR and fat percentage in this study (0.53) was found to be more similar to the average correlation between D[4,3] and fat percentage (0.54) than the correlation between MIR-predicted D[4,3] and fat percentage (0.97) reported previously by Fleming et al (2017b). Additionally, standard deviations estimated for the correlations of MFGS MIR with fat percentage and other milk components were significantly lower in this study than the ones reported previously by Fleming et al (2017b), who used records from 254 cows in 29 herds. Therefore, one could speculate that the prediction equation generated by Fleming et .…”
Section: Genetic Correlationssupporting
confidence: 86%
See 4 more Smart Citations
“…The average genetic correlation between MFGS MIR and fat percentage in this study (0.53) was found to be more similar to the average correlation between D[4,3] and fat percentage (0.54) than the correlation between MIR-predicted D[4,3] and fat percentage (0.97) reported previously by Fleming et al (2017b). Additionally, standard deviations estimated for the correlations of MFGS MIR with fat percentage and other milk components were significantly lower in this study than the ones reported previously by Fleming et al (2017b), who used records from 254 cows in 29 herds. Therefore, one could speculate that the prediction equation generated by Fleming et .…”
Section: Genetic Correlationssupporting
confidence: 86%
“…The average heritability throughout lactation for MFGS MIR from the 2 multivariate analyses is shown in Table 2 and was estimated at 0.46. This estimated value was higher than the value estimated in a previous study by Fleming et al (2017b), in which the mean estimated heritability for MIR-predicted volume moment mean (D[4,3]) was 0.30 (SE = 0.17). Fleming et al (2017b) analyzed only a subset of the records used in the present study, which may explain the variation in estimates.…”
Section: Heritability Estimatescontrasting
confidence: 79%
See 3 more Smart Citations